2020
DOI: 10.1002/alr.22561
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of topical intranasal cocaine for sinonasal procedures: a randomized, phase III clinical trial

Abstract: Background: The objective of this trial was to demonstrate the clinical efficacy and safety of topical cocaine as part of the effort to gain regulatory approval from the United States Food and Drug Administration. Methods: This phase III, randomized, prospective, double-blind, multicenter, single-dose, placebo-and dosecontrolled, parallel-group study aimed to evaluate the safety and efficacy of topical intranasal cocaine (RX0041-002). A total of 925 subjects were screened and a total of 648 subjects were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As cited by McGrath et al., 1 a direct comparison of oxymetazoline and lidocaine shows it to be as effective as cocaine with a longer duration of analgesic effects 3 . Results for tetracaine and oxymetazoline are similar in comparison to cocaine 4 .…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…As cited by McGrath et al., 1 a direct comparison of oxymetazoline and lidocaine shows it to be as effective as cocaine with a longer duration of analgesic effects 3 . Results for tetracaine and oxymetazoline are similar in comparison to cocaine 4 .…”
mentioning
confidence: 71%
“…We reviewed the article by McGrath et al 1 . with great interest, but would like to raise some concerns, many of which were previously articulated when Long et al 2 .…”
mentioning
confidence: 99%
“…Recently, a study found that topical 4% and 8% cocaine is an effective anesthetic that can be safely administered for nasal procedures based on a randomized phase III clinical trial. This study aims to favor approval by the United States Food and Drug Administration (FDA) because many otolaryngologists frequently utilize topical cocaine in their practice [4]. For example, in a large survey of active members of the American Academy of Otolaryngology-Head and Neck Surgery, which was published in 2004, fifty percent of respondents reported using cocaine as a topical agent during endoscopic sinus surgery over the preceding calendar year [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, these changes were transient and inconsequential. There were no major adverse events such as arrhythmia nor cardiac arrest 5 …”
mentioning
confidence: 95%
“…We also reiterated the notion that the use of topical cocaine in conjunction with other vasoconstrictive agents (ie, epinephrine) can produce adverse events. Thus is should be avoided in patients with significant cardiac histories 5 . We feel that Francis et al., 1 who are at a large academic institution with a well‐known otolaryngology department, should have consulted with these individuals regarding their usage of cocaine.…”
mentioning
confidence: 99%